Evidence for shared molecular pathways of dysregulated decidualization in preeclampsia and endometrial disorders revealed by microarray data integration. Issue 11 (7th August 2019) - Rabaglino, Maria Belen; Conrad, Kirk P.
Abstract : Microarray data of chorionic villous samples (CVSs) obtained from women of 11.5 gestational weeks who developed preeclampsia with severe features (sPE; PE‐CVS) revealed a molecular signature of impaired endometrial maturation (decidualization) before and during early pregnancy. Because endometrial disorders are also associated with aberrant decidualization, we asked whether they share molecular features with sPE. We employed microarray data integration to compare the molecular pathologies of PE‐CVS and endometrial disorders, as well as decidua obtained postpartum from women with sPE. Eight public databases were reanalyzed with R software to determine differentially expressed genes (DEGs) in pathologic tissues relative to normal controls. DEGs were then compared to explore overlap. Shared DEGs were examined for enriched Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Principal component and network analyses were subsequently applied to selected DEGs. There was significant overlap of DEGs changing in the same direction for PE‐CVS and endometrial disorders, suggesting common molecular pathways. Shared DEGs were enriched for cytokine‐cytokine receptor interaction. Genes in this pathway revealed expression patterns forming 2 distinct clusters, one for normal and the other pathologic endometrium. The most affected hub genes were related to decidualization and NK cell function. Few DEGs were shared by PE‐CVS, and PE decidua obtained postpartum. sPE may be part of a biologic continuum of "endometrial spectrum disorders."—Rabaglino, M. B., Conrad, K. P. Evidence for shared molecular pathways of dysregulated decidualization in preeclampsia and endometrial disorders revealed by microarray data integration. FASEB J. 33, 11682‐11695 (2019). www.fasebj.org